Analisis Wacana Kritis Pemberitaan Peresmian Masjid Al Bakrie Lampung pada Portal Berita NU Online - Permata Mulia Bhakti; Fariza Makmun; Apun Syaripudin (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to reveal how the construction of discourse, ideology, and power relations are represented in the news coverage of the inauguration of the Al Bakrie Mosque in Lampung on NU Online. The method used is a qualitative approach with Norman Fairclough's critical discourse analysis technique which includes three dimensions, namely text analysis, discursive practice, and social practice. The results show that in the text dimension, NU Online uses religious diction, narrative structure, and persuasive language style to build a positive image of the mosque as a symbol of Islamic progress. In the discursive practice dimension, news production and distribution reflect the function of digital da'wah that emphasizes moderate Islamic values, while text consumption strengthens the acceptance of messages by audiences who have ideological closeness. In the social practice dimension, the news coverage shows the relationship between religion and the state, the reproduction of moderate Islamic ideology, and the integration of Islamic values ​​with local culture. This study contributes to understanding the role of Islamic media as an effective digital da'wah tool in shaping public opinion and spreading Islamic values ​​in the public sphere.